ELECTROCARDIOGRAPHIC PROFILE OF DILATED CARDIOMYOPATHY IN PATIENTS ATTENDING A TERTIARY CARE HOSPITAL OF WESTERN NEPAL - Kafle, Ram Chandra; Paudel, Navaraj; Sharma, Dibya; Alurkar, Vijaya Madhav (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Cardiomyopathy is a disease of the heart muscle that leads to deterioration of myocardial functioning. It has different morphological variation with dilated cardiomyopathy being the most common form comprising over 90% of all cases. Heart failure (HF) is the most common clinical presentation of dilated cardiomyopathy. Various electrocardiographic changes are common in these patients. The most common cause of sudden death in these patients is arrhythmia. This study aimed at characterizing different electrocardiographic changes in patients of dilated cardiomyopathy admitted for heart failure. MATERIAL AND METHODS: A retrospective analysis of records of admitted patients from l" January 2015 to 30th April 2018 was conducted. Study was conducted after obtaining ethical clearance from institutional review board. Data was collected in a preformed proforma and analyzed using SPSS 20.0 version. RESULTS: Consecutive 400 cases of dilated cardiomyopathy with systolic dysfunction (LVEF<40%) were taken for the study. Two hundred and fifty two (63 %) were male. The mean age of patients was 59.33 (± 15.76) years. The most common risk factors in our patients were smoking (66%) followed by systemic hypertension (49%), IHD (32%), and diabetes mellitus (33%) respectively. Out of 400 patients, abnormal ECG were found in 82.5%. The most common abnormality was LVH (30.7%) followed by LBBB (22.5%) and AF (20.5%). CONCLUSION: The percentage of abnormal electrocardiographic findings was high in our study. All patients of dilated cardiomyopathy should undergo electrocardiography screening for risk stratification and to prevent serious consequences with early necessary intervention. Journal of Universal College of Medical Sciences Vol. 6, No. 1, 2018, Page: 40-45